Erosion of beta diversity under interacting global change impacts in a semi‐arid grassland. (19th January 2015) - Eskelinen, Anu; Harrison, Susan; Schwinning, Susan
Summary Human impacts are often thought of as homogenizing natural communities, but it is unclear how these impacts interact to alter the beta diversity (spatial variability) of plant communities. In a grassland with high beta diversity along a soil fertility gradient, we asked which combinations of nutrient enrichment, precipitation enhancement and disturbance would homogenize communities along the gradient by allowing dominant species from one part of the gradient to increase their abundances in other parts of the gradient. In particular, joint addition of nutrients and water might especially benefit resource‐acquisitive and/or exotic species, which have been observed to compete well in resource‐rich conditions; this would tend to reduce variation in species composition across the gradient. To alleviate dispersal limitation as a constraint on treatment responses, we added seeds of 15 species abundant in different parts of the soil fertility gradient to our 132 plots. Fertilization and water addition allowed species from fertile soils to increase their abundance in infertile soils, an effect that strengthened with time. Disturbance permitted species from infertile soils to increase in abundance in infertile soils, but only transiently. Plant height, specific leaf area and exotic status best predicted the abilities of species to attain greater cover in harsh habitats under ameliorated conditions. Among‐habitat beta diversity of seeded species was reduced by the interactive effect of fertilization and watering, although not by watering alone. Synthesis. Our findings are a novel demonstration of how interacting global change factors reduce beta diversity by eroding the biotic and abiotic resistances that control community structure along soil fertility gradients.